2000
DOI: 10.1007/s004150070089
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomographic angiography findings in 103 patients following vascular events in the posterior circulation; potential and clinical relevance

Abstract: We studied the diagnostic value of computed tomographic angiography (CTA) in the posterior circulation as a noninvasive substitute for intra-arterial digital subtraction angiography (DSA). We prospectively investigated 103 patients with acute stroke in the posterior circulation. All patients underwent CTA and Doppler ultrasound, and DSA was performed in 22 patients. Vascular findings were classified in categories according to the type of lesion and the location in the vertebral, basilar, or posterior cerebral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 15 publications
0
25
0
1
Order By: Relevance
“…Had these studies been relied upon solely, the patient would have been at substantial risk of morbidity and even mortality. Previous studies have demonstrated the limitations of MRA and CTA in imaging the posterior circulation [9,10]. Our patient illustrates that conventional angiogram remains the gold standard for visualizing the posterior circulation, because both CTA and MRA failed to identify the fenestrated vessels.…”
Section: Case Reportmentioning
confidence: 76%
“…Had these studies been relied upon solely, the patient would have been at substantial risk of morbidity and even mortality. Previous studies have demonstrated the limitations of MRA and CTA in imaging the posterior circulation [9,10]. Our patient illustrates that conventional angiogram remains the gold standard for visualizing the posterior circulation, because both CTA and MRA failed to identify the fenestrated vessels.…”
Section: Case Reportmentioning
confidence: 76%
“…242, 252 The accuracy of CTA for evaluation of large-vessel intracranial stenoses and occlusions is very high, [253][254][255][256] and in some cases its overall accuracy approaches or exceeds that of digital subtraction angiography (DSA). 253, 257 The sensitivity and specificity of CTA for the detection of intracranial occlusions ranges between 92% and 100% and between 82% and 100%, respectively, with a positive predictive value of 91% to 100%.…”
Section: Ct Angiographymentioning
confidence: 99%
“…202,210,212,219 "Core" ischemia can be defined accurately by perfusion CT depending on equipment and programming. Various studies have used different hemodynamic parameters, such as mean transit time, cerebral blood volume, and cerebral blood flow, [252][253][254][255][256][257][258]260,[264][265][266][267][268][269][270][271][272][273][274][275]350 different thresholds for determining hemodynamic abnormality (eg, degree of reduction in cerebral blood volume and absolute versus relative threshold), and different thresholds for the amount of penumbral tissue that warrants treatment (eg, 20%, 100%, or 200% the size of the infarct core). 206,207,213,[215][216][217][347][348][349] The International Stroke Imaging Repository (STIR) consortium is currently addressing these issues and is attempting to standardize imaging methodology, processing, and interpretation.…”
Section: Perfusion Ct and Mrimentioning
confidence: 99%
“…Few studies have examined the accuracy of CTA to detect and quantify intracranial arterial stenosis. [15][16][17] We sought to examine the accuracy of CTA in evaluating ICAD as compared with DSA as the gold standard.…”
mentioning
confidence: 99%